ANALISIS SENTIMEN LPDP (LEMBAGA PENGELOLA DANA PENDIDIKAN) PADA MEDIA SOSIAL TWITTER - Samuel Adhi Bagaskoro; Atin Hasanah; Saiful Bahri; Ema Utami; Ainul Yaqin (UNIB Press, 2023)
LPDP Scholarship (Education Fund Management Institution) is the most sought after by prospective students who want to continue their studies in the country, especially for those who want to continue their studies abroad. Recently, LPDP experienced problems related to students who received LPDP scholarships but did not return to Indonesia in accordance with the rules that have been stated. Starting from the incident on twitter, the topic of